2019
DOI: 10.3390/nu11061344
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Food Processing Classification Systems

Abstract: Discrepancies exist among food processing classification systems and in the relationship between processed food intake and dietary quality of children. This study compared inter-rater reliability, food processing category, and the relationship between processing category and nutrient concentration among three systems (Nova, International Food Information Council (IFIC), and University of North Carolina at Chapel Hill (UNC)). Processing categories for the top 100 most commonly consumed foods children consume (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 43 publications
5
44
0
3
Order By: Relevance
“…The UNC framework incorporates expanded processing categories ( Table 1 ). Several studies have demonstrated that the UNC system has the highest inter-rater reliability compared to other classification systems using European [ 14 ] and U.S. food samples [ 15 ]. As described by the authors of NOVA, the systems were developed to “group foodstuffs according to the extent and purpose of the industrial processing applied to them [ 12 ]”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UNC framework incorporates expanded processing categories ( Table 1 ). Several studies have demonstrated that the UNC system has the highest inter-rater reliability compared to other classification systems using European [ 14 ] and U.S. food samples [ 15 ]. As described by the authors of NOVA, the systems were developed to “group foodstuffs according to the extent and purpose of the industrial processing applied to them [ 12 ]”.…”
Section: Introductionmentioning
confidence: 99%
“…The NOVA and other processing classification systems have received extensive criticism from the scientific community regarding their consistency [ 19 ], reliability [ 14 , 15 ], validity [ 14 , 15 ], and policy implications [ 19 , 20 ]. Importantly, misclassification of home-prepared foods as their store-bought equivalent may lead to inappropriate associations of home-cooked items with less desirable health outcomes or misrepresentation of nutrient profiles associated with highly processed food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-processed food is subjected to multidirectional processes and modifications prior to consumption and contains significant amounts of added sugar, salt, saturated fat and number of additives per product. Currently, there is no clear classification system or definition describing processing levels and categories reflecting real nutrient loading, which could increase applicability and efficiency in public health improvement [10].…”
mentioning
confidence: 99%
“…According to Monteiro et al [9,11], ultra-processed food has been defined as the result of a series of processing operations carried out in order to obtain a formulation mostly from cheap sources of energy, nutrients and selected additives, thus containing minimal whole foods. The NOVA food classification system has been among those most often applied in scientific research, however, it may not sufficiently identify foods with high nutrient quality commonly consumed by children in the U.S. [10]. It categorizes foods and beverages into four groups: unprocessed or minimally processed foods, processed culinary ingredients, processed foods and ultra-processed foods.…”
mentioning
confidence: 99%
“…On the other hand, among the various stakeholders (producers, scientists, governmental agencies like FAO/WHO, and consumers), a substantial discrepancy exists about the understanding and interpretation of various food processing classification systems (Bleiweiss-Sande et al, 2019). While the NOVA system divides processing of foods into four categories (Monteiro et al, 2010), the IFIC systems identifies five categories (International Food Information Council Foundation, 2010), and the UNC divides it even into seven categories of processing (Poti et al, 2015).…”
Section: Exploration Of Consumers' Health Perception Of Dried Mango: mentioning
confidence: 99%